STRATEGI PERENCANAAN PENGEMBANGAN PARIWISATA UNTUK MEWUJUDKAN DESTINASI TANGGUH BENCANA DI WILAYAH KEPESISIRAN DRINI GUNUNGKIDUL - Muhammad Rizal Pahleviannur; Diyah Ayu Wulandari; Salma Lutfiani Sochiba; Ramadhini Rudi Santoso (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
The coastel region in Indonesia is one of the densest areas of settlement and development, even some of the major cities in Indonesia located in the coastel area and become a major tourism destination. However, behind the beauty there is a threat in the form of natural disasters, if the management of tourism is not optimal for facilities and infrastructure can increase the risk of disaster. This study aims to recommend planning for disaster based tourism development with structural mitigation. This research is a qualitative research. The data collection method used in this research is to conduct literature studies, observations, and documentation. The result of this study indicate that the facilities and infrastructure available at Drini Beach are classified as incomplete in terms of structural mitigation against disaster, so there is a need for planning in developing disaster resilient tourism, with the aim of creating a friendly an resilient tourism climate.